Immunotherapy against murine experimental visceral leishmaniasis with the FML-vaccine - Santos, W. R.; Aguiar, I. A.; de Souza, E. P.; de Lima, VMF; Palatnik, M.; Palatnik-de-Sousa, C. B. (Elsevier B.V., 2003)
The fucose mannose ligand (Leishmania donovani FML)-saponin vaccine has earlier shown its immunoprophylactic potential against visceral leishmaniasis in the CB hamster (87.7% of parasite load reduction), Balb/c (84.4%) and Swiss albino mouse (85-93%) models. In this investigation its specific immunotherapeutic efficacy against L. donovani infection in Balb/c mice was studied. The effects of vaccine treatment on the Immoral response, delayed type of hypersensitivity to promastigote lysate (DTH), cytokine levels in sera and reduction of the liver parasitic load of L. donovani infected mice, were examined. The types and subtypes of anti-FML antibodies increased significantly in the vaccinees over the saline and saponin controls. As expected for a saponin vaccine, the highest ratios were found in relation to IgG1, IgG2a and IgG2b (4.4, 5 and 2.5, respectively). The DTH response and the in vitro ganglion cell proliferative response against FML antigen were also significantly higher than controls (P < 0.005). Concomitantly, an impressive and specific decrease of liver parasitic burden was detected only in vaccine-treated animals (94.7%). Our results indicate that the therapeutic FML-vaccine has a potent effect on modulation of the murine infection leading to the reduction of parasitic load and signs of disease, being a new potential tool in the therapy and control of visceral leishmaniasis. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: visceral leishmaniasis; kala-azar; FML-vaccine; immunotherapy; immunoprophylaxis; saponin; vaccination